Tracking sea bed topography in the Jurassic. The Lotena Group in the Sierra de la Vaca Muerta (Neuquén Basin, Argentina) - Zavala, Carlos Alberto (2005)
The Lotena Group is a clastic to evaporitic unit up to 650 m thick that accumulated during the Middle to Late Jurassic in the Neuquén Basin, western Argentina. Extensive field work carried out in the Sierra de la Vaca Muerta and Arroyo Covunco areas, including the measurement of seven detailed stratigraphic sections and geo- logical mapping allow the discrimination of six unconformity-bounded units or sequences. The first sequence is composed of red beds and evaporites belonging to the Tábanos Formation that unconformably overlies strata of the Lower to Middle Jurassic Cuyo Group. Sequences 2 to 5 are shallow marine and display a basal sandstone interval attributed to confined shelfal sandstone lobes. These grade vertically into unconfined shelfal sandstone lobes, and terminate with carbonate deposits. The basal interval is restricted to the thickest areas of each sequence, a relationship attributed to structural relief. Sequence 6 has a very irregular shape and strongly trun- cates the underlying deposits. It is composed almost entirely of massive carbonate strata that were deposited by density currents. Facies analysis and stratigraphic mapping suggest periodic recycling of previous accumula- tions. Stratigraphic evidence suggests that the Lotena Group in the Sierra de la Vaca Muerta and adjacent areas probably accumulated over a tectonically unstable basement. Sequences 1, 2 and 3 display evidence of accumu- lation in an extensional tectonic setting, while sequences 4, 5 and 6 experienced a northward shift of their depocentres associated with extensive erosional truncation of the marginal areas, suggesting that accumulation was affected by early stages of growth of the Covunco anticline.